Secure Data Communications using Cryptography and IPv6 Steganography - A. Muhajjar, Ra’ad; A. Badr, Farah; ., . (International Journal of Engineering and Technology, 2018)
Security is an important topic in any communication especially if the communicating endpoints have confidential data and require utilizing special techniques to protect it. In this research paper, cryptography method was combined with steganography to enable sending confidential data by utilizing IPv6 protocol header as a cover to conceal secret messages. Flow label field is the field that will be used as a covert channel to exchange critical data between the endpoints. To generate the encryption/decryption key, a proposed pseudo-random number generator was applied. The generated numbers show good statistics when tested using standard statistical tests. In cryptography, RC6 was executed in CBC mode to encrypt/decrypt N blocks of data. For origin authentication, a proposed MAC was implemented to the encrypted data to obtain MAC value that will be sent along with the encrypted data to the receiving endpoints. After obtaining the encrypted data and the MAC, both will be embedded in IPv6 flow label field.
Keywords: Data Hiding; Cryptography; Steganography; Network Steganography; TCP/IP.